The predictive value of mean platelet volume, plateletcrit and red cell distribution width in the differentiation of autoimmune gastritis patients with and without type I gastric carcinoid tumors. (August 2014) - Tüzün, Ali; Keskin, Onur; Yakut, Mustafa; Kalkan, Cagdas; Soykan, Irfan
Abstract Autoimmune gastritis is an autoimmune and inflammatory condition that may predispose to gastric carcinoid tumors or adenocarcinomas. The early diagnosis of these tumors is important in order to decrease morbidity and mortality. Platelet indices such as mean platelet volume and plateletcrit levels increase in inflammatory, infectious and malign conditions. The primary aim of this study was to explore wheter platelet indices and red cell distribution width have any predictive role in the discrimination of autoimmune gastritis patients with and without gastric carcinoid tumors. Also secondary aim of this study was to investigate whether any changes exist betwenn autoimmune gastritis and functional dyspepsia patients by means of platelet indices. Plateletcrit (0.22 ± 0.06 vs. 0.20 ± 0.03%, p < 0.001) and red cell distribution width (16.11 ± 3.04 vs. 13.41 ± 0.95%, p < 0.001) were significantly higher in autoimmune gastritis patients compared to control group. Receiver operating curve analysis suggested that optimum plateletcrit cut-off point was 0.20% (AUC: 0.646), and 13.95% as the cut off value for red cell distribution width (AUC: 0.860). Although plateletcrit (0.22 ± 0.06 vs. 0.21 ± 0.04%, p = 0.220) and mean platelet volume (8.94 ± 1.44 vs. 8.68 ± 0.89 fl, p = 0.265) were higher in autoimmune gastritis patients without carcinoid tumor compared to patients with carcinoid tumors, these parameters were not statistically significant. Changes in plateletcrit and red cell distribution width values may be used as a marker in the discrimination of autoimmune gastritis and fucntional dyspepsia patients but not useful in patients with gastric carcinoid tumor type I.